Answer:
( x^2 - 6 )^2
Step-by-step explanation:
- Find one factor
- Factor by grouping
*solution* ( x^2 - 6 )^2
Answer:
A, B, F
Step-by-step explanation:
2/3 - x + 1/6 = 6x
Collect like terms
2/3 + 1/6 = 6x + x
(4+1) / 6 = 7x
5/6 = 7x
x = 5/6 ÷ 7
= 5/6 × 1/7
x = 5/42
a) 4 - 6x + 1 = 36x
4 + 1 = 36x + 6x
5 = 42x
x = 5/42
Equivalent to the last step of the simplification above
b) 5/6 - x = 6x
5/6 = 6x + x
5/6 = 7x
This is equivalent to the third step of the simplification
c) 4 - x + 1 = 6x
4 + 1 = 6x + x
5 = 7x
x = 5/7
Not equivalent to any of the steps in the simplification above
d) 5/6 + x = 6x
5/6 = 6x - x
5/6 = 5x
x = 5/6 ÷ 5
= 5/6 × 1/5
x = 5/30
Not equivalent to any of the steps in the simplification above
e) 5 = 30x
x = 5/30
Not equivalent to any of the steps in the simplification above
f) 5 = 42x
x = 5/42
Equivalent to the last step of the simplification above
Step-by-step explanation:
6:8=9:12=12:16=15:20
Answer: The detergent for <u><em>$5.50 for 96 oz</em></u> is better.
Step-by-step explanation:
128 ÷ $6.90 ≈ 18.55
96 ÷ $5.50 ≈ 17.45
ANSWER: Plane dropped 6097 feet in altitude.
BECAUSE: An airplane is at point A from where it continued to descend by 30° for an approximate distance of 2 miles
∠ACB = Angle of descent = 30°
Distance BC = 2 miles
Let the plane dropped the altitude = h miles
Now tan 30° =
h = 1.155 miles
h ≈ 1.16 miles
Since 1 mile = 5280 feet
1.15 miles = 5280×1.16 feet
= 6097 feet
Therefore, the plane dropped by 6097 feet vertically.